2023
DOI: 10.1099/mic.0.001340
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms as protective cocoons against biocides: from bacterial adaptation to One Health issues

Abstract: Bacteria in the food chain mostly live in communities associated with surfaces known as biofilms, which confer specific survival and adaptive abilities. In such communities, the bacteria mostly exhibit higher tolerance to external stress, and their recurrent exposure along the food chain to biocides used during cleaning and disinfection procedures raises concern about the adaptation routes they develop, both at single-cell and communal levels. In recent years, an increasing number of research subjects have foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 218 publications
(316 reference statements)
0
6
0
1
Order By: Relevance
“…SOS-induced nucleic acid release and protein release were inhibited by zinc salts, the NO donor SNAP, and dequalinium. In addition to triggering emergence of new antibiotic resistance via hypermutation, the SOS-induced biofilm formation may also affect resistance by reducing penetration of drugs into the biofilm [ 6 ], by decreased metabolic activity of bacteria due to limited oxygen or nutrients, and by many other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOS-induced nucleic acid release and protein release were inhibited by zinc salts, the NO donor SNAP, and dequalinium. In addition to triggering emergence of new antibiotic resistance via hypermutation, the SOS-induced biofilm formation may also affect resistance by reducing penetration of drugs into the biofilm [ 6 ], by decreased metabolic activity of bacteria due to limited oxygen or nutrients, and by many other factors.…”
Section: Discussionmentioning
confidence: 99%
“…The SOS response had previously been implicated as a trigger of biofilm formation, but the role of DNA in the biofilms was not appreciated [ 5 ]. Bacterial biofilms have been recognized as sanctuary sites in which emergence of antimicrobial resistance occurs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resistant variants appear naturally in bacterial populations and could be preferentially selected in Ec709 by the biofilm lifestyle itself rather than biocidal exposure. This can be related to particular chemical microenvironments in the three-dimensional structure of Ec709 biofilm that could participate in the induction of specific phenotypes and/or selection of genetic variants ( Uruén et al., 2020 ; Charron et al., 2023 ). In addition, recent findings showed that hypermutator emergence rates are dependent of stress type in E. coli populations ( Callens et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike antibiotics, which often have specific targets in the bacterial cell, biocides typically employ a multi-targeted mode of action. However, mechanisms developed by bacteria to resist biocides can be close or imply common cellular components to those involved in antibiotic resistance and multiple possible cross-resistances have already been identified in different bacterial species ( Maillard, 2018 ; Charron et al., 2023 ). Schematically, when exposing bacteria to a biocide, cross-adaptations could result from two major types of mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation